2012
DOI: 10.1080/15433714.2012.636327
|View full text |Cite
|
Sign up to set email alerts
|

Building Organizational Supports for Research-Minded Practitioners

Abstract: One of the biggest challenges facing human service organizations is the proliferation of information from inside and outside the agency that needs to be managed if it is to be of use. The concepts of tacit and explicit knowledge can inform an approach to this challenge. Tacit knowledge is stored in the minds of practitioners (often called practice wisdom) and the explicit knowledge is often found in organizational procedure manuals and educational and training materials. Building on this perspective, this anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…These barriers include bureaucratic or rigid organizational structures, organizational cultures and climates that are resistant to research and experimentation, and/or the lack of time and fiscal resources needed for staff training for implementing evidence-informed practice . In this era of increasing accountability for social services, there has been an ongoing search for ways to model evidence-informed practice, create learning environments, construct knowledge-sharing communities, and promote a culture of ongoing practice improvement to support the capacities of practitioners to integrate research and practice (Austin, Dal Santo, & Lee, 2012;Gray, 2009;Plath, 2014;Raffel, Lee, Dougherty, & Greene, 2013). Some of the knowledge brokering tasks needed to strengthen the development of learning organizations include the capacity to (1) identify, evaluate, and translate research for use in different practice settings (Jackson-Bowers, Kalucy, & McIntyre, 2006;Lomas, 2007;Meyer, 2010;Waring, Currie, Crompton, & Bishop, 2013); (2) apply relevant research to specific practice settings (Jackson-Bowers et al, 2006;Kramer, Cole, & Leithwood, 2004;Lomas, 2007;Meyer, 2010;Waring et al, 2013); (3) build research-focused relationships between practitioners and researchers (Jackson-Bowers et al, 2006;Lomas, 2007;(4) build the research capacity of staff (Meyer, 2010;Rivard et al, 2010;Traynor, DeCorby, & Dobbins, 2014); and (5) manage research resources and data (Jackson-Bowers et al, 2006).…”
Section: Link Officers As Boundary-spanning-knowledge Brokersmentioning
confidence: 99%
“…These barriers include bureaucratic or rigid organizational structures, organizational cultures and climates that are resistant to research and experimentation, and/or the lack of time and fiscal resources needed for staff training for implementing evidence-informed practice . In this era of increasing accountability for social services, there has been an ongoing search for ways to model evidence-informed practice, create learning environments, construct knowledge-sharing communities, and promote a culture of ongoing practice improvement to support the capacities of practitioners to integrate research and practice (Austin, Dal Santo, & Lee, 2012;Gray, 2009;Plath, 2014;Raffel, Lee, Dougherty, & Greene, 2013). Some of the knowledge brokering tasks needed to strengthen the development of learning organizations include the capacity to (1) identify, evaluate, and translate research for use in different practice settings (Jackson-Bowers, Kalucy, & McIntyre, 2006;Lomas, 2007;Meyer, 2010;Waring, Currie, Crompton, & Bishop, 2013); (2) apply relevant research to specific practice settings (Jackson-Bowers et al, 2006;Kramer, Cole, & Leithwood, 2004;Lomas, 2007;Meyer, 2010;Waring et al, 2013); (3) build research-focused relationships between practitioners and researchers (Jackson-Bowers et al, 2006;Lomas, 2007;(4) build the research capacity of staff (Meyer, 2010;Rivard et al, 2010;Traynor, DeCorby, & Dobbins, 2014); and (5) manage research resources and data (Jackson-Bowers et al, 2006).…”
Section: Link Officers As Boundary-spanning-knowledge Brokersmentioning
confidence: 99%
“…Practitioner characteristics such as openness to new ideas and having a positive attitude toward change have been associated with higher use of new information (Austin, Dal Santo, & Lee, 2012;Damanpour & Schneider, 2009). Studies have also found that managers in positions of authority with strong professional networks and with access to organizational resources are more-active innovators (Hage & Dewar, 1973;Rycroft-Malone et al, 2002;Wilson, 1966).…”
Section: Managerial Factors That Influence Innovationmentioning
confidence: 96%
“…A critical support is the availability of knowledge-sharing teams that facilitate the locating, appraising, and use of diverse types of evidence to support managerial decision making (Austin et al, 2012). The connection between evidence-informed management practice and the social network aspects of human service innovation is the development of these communities of learning.…”
Section: Managerial Factors That Influence Innovationmentioning
confidence: 99%
“…This basic finding is supported by other studies referenced in the systematic review conducted by Kroll (2014) as well as research on practitioner evidence use in the human service sector (Palinkas et al, 2011). Research has identified other mechanisms through which agency leaders involve themselves in evidence-informed practice due to the likelihood that they (a) serve as agency representatives for research-based initiatives involving external researchers; (b) are formally responsible for searching for promising practices and identifying evidence-based strategies for responding to current agency dilemmas; (c) oversee data collection and reporting with respect to performance measurement; and (d) organize within-agency communities of learning around professional development and research evidence due to their knowledge of the needs of organizational divisions and key staff (Aarons et al, 2011;Austin et al, 2012;Maynard, 2010).…”
Section: Organizational Factors Promoting Access To Evidencementioning
confidence: 99%
“…Practitioners are also likely to use evidence if they are given time to explore research, discretion Downloaded by [Portland State University] at 11:59 18 September 2015 and training to engage with diverse types of evidence, and access to external and internal evidence (Doran et al, 2012;Gray, Joy, Plath, & Webb, 2013). These studies imply that managerial evidence use requires dedicated resources and organizational commitment to be sustained effectively (Austin, Dal Santo, & Lee, 2012). As a result, this question supports the identification of promising approaches to promote the development of evidence-informed human service managers.…”
mentioning
confidence: 99%